Molecular characterization of Bombyx mori (Lepidoptera: Bombycidae) strains by AFLP - GAVIRIA-A., DUVERNEY; AGUILAR-F., ENRIQUE; RAMÍREZ-L., LILIANA; ALEGRÍA-S., ÁLVARO (Revista Colombiana de Entomología, 2006)
Twenty-three silkworm Bombyx mori L. strains (twelve Japanese and eleven Chinese strains), belonging to the CDTS (Technological Development Center for Sericulture) silkworm germplasm bank, were analyzed using the Amplified Fragment Length Polymorphism (AFLP) technique. Four combinations of primers were used. The four assayed combinations produced 247 bands with an average polymorphism of 54,6%; which, when corrected using Lynch and Milligan’s criteria, resulted in 168 bands with a polymorphism of 90,4%. The dendrogram was built using the UPGMA algorithm for the dissimilarity data, revealing two very well defined groups that correspond to the Japanese and Chinese geographical races. The heterozigocity average was higher in the Japanese race lines, showing a greater dispersion in the UPGMA and the main components analysis. The population structure study indicate that although the two races are not very different from each other, there exists a component of greater variance between the established groups than within them, which shows a significant level of genetic differentiation.